Objective monitoring of disease activity in polyarteritis by measurement of serum C reactive protein concentration. Issue 6423 (7th April 1984) - Hind, C R; Savage, C O; Winearls, C G; Pepys, M B
Abstract : Serial measurements of the serum concentration of C reactive protein were made in 27 patients with polyarteritis over six years. The concentration was invariably raised when the disease was active, even in patients receiving immunosuppressive treatment, and fell rapidly in association with clinical remission induced by immunosuppression. During periods of complete remission, in the absence of any intercurrent condition, the value remained within the normal range. The correlation between C reactive protein concentration and disease activity was much closer than that between erythrocyte sedimentation rate and disease activity. These results indicate that serial measurement of the serum C reactive protein concentration fills the urgent need for an objective index of the activity of polyarteritis and its response to treatment.